Capacity building for LAZIS administration through Google Applications Training - Yuliansyah, Herman; Fahana, Jefree; Prahara, Adhi; Masitha, Alya (Institut Teknologi Dirgantara Adisutjipto, 2025)
The rapid development of information technology has prompted social institutions such as LazisMU to adopt digital administrative systems. However, technical limitations among staff hinder optimal implementation. This community service aimed to enhance the administrative capacity of LazisMU staff through targeted training in Google Applications. The training involved needs assessment, module development, and interactive sessions covering Google Drive, Docs, Sheets, and Forms. Results indicate significant improvement in participants’ understanding and skills, particularly in document management, financial reporting, and data handling. Pre-test and post-test comparisons, along with direct observation, showed over 60% improvement in comprehension scores. These outcomes highlight the positive impact of digital training on operational efficiency. Further training and periodic monitoring are recommended to ensure continued digital competence development.